(untitled) (International Current Pharmaceutical Journal, 2016)
Cardiovascular diseases (CVDs) have increased the mortality rate both in developing as well as developed countries, however a lower trend in death rates have been seen in developed and high income countries like USA, UK, Australia, Japan and other European countries due to improved life style, better strategic implementation, control of disease both in young and adults and especially reduced smoking habits. In developing countries CVD become an alarming situation due to prevalence of disease in early age that later on become chronic and difficult to control. Various risk factors that can contribute toward CVD in developing countries include smoking, high alcohol and salt intake, dietary factors, diabetes, high blood pressure and psychosocial aspects such as stress, anxiety and depression. Various other factors such as family history and the gender difference also contributing towards the high risk of developing CVD. Rehan et al., International Current Pharmaceutical Journal, July 2016, 5(8): 69-72 http://www.icpjonline.com/documents/Vol5Issue8/02.pdf